Down-conversion emission of Ce3+-Tb3+ co-doped CaF2 hollow spheres and application for solar cells. (28th March 2018) - Cheng, Yufei; Wang, Yongbo; Teng, Feng; Dong, Hua; Chen, Lida; Mu, Jianglong; Sun, Qian; Fan, Jun; Hu, Xiaoyun; Miao, Hui
Abstract: Luminescent downconversion is a promising way to harvest ultraviolet sunlight and transform it into visible light that can be absorbed by solar cells, and has potential to improve their photoelectric conversion efficiency. In this work, the uniform hollow spheres and well dispersed CaF2 phosphors doped with rare-earth Ce 3+ and Tb 3+ ions are prepared by a one-step hydrothermal synthesis method. Benefiting from the stronger ability of absorption and emission and excellent transparency property, we demonstrate that the application of the doped nanocrystals can efficiently improve visible light transmittance. The chosen phosphors are added in the SiO2 sols so as to get the anti-reflection coatings with wavelength conversion bi-functional films, promoting the optical transmittance in the visible and near-infrared range which matches with the range of the band gap energy of silicon semiconductor. Optimized photoelectric conversion efficiency of 14.35% and the external quantum efficiency over 70% from 450 to 950 nm are obtained through the silicon solar cells with 0.10 g phosphors coating. Compared with the pure glass devices, the photoelectric conversion efficiency is enhanced by 0.69%. This work indicates that fluorescent downconversion not only can serve as proof of principles for improving photoelectric conversion efficiency of solar cells but also may be helpful to practical application in the future.